PENINGKATAN SOPAN SANTUN PESERTA DIDIK PASCA PEMBELAJARAN DARING PADA PTM TERBATAS - Fatimah Q A'ini; Yusuf Falaq (Social Landscape Journal, 2022)
Education is a pillar of the establishment of a nation and state. Education is a bridge for humans to avoid oppression, ignorance and backwardness. Educators are required to be able to guide, direct and educate students to be smart in science and good in morals. Morality is very important in social life, especially for children at junior high school age. In this study, the researcher used a qualitative method with a case study approach. Educators have roles as organizers and initiators in charge of compiling and designing syllabus and lesson plans that will be used in the teaching and learning process later. In the RPP there is already a learning plan that will be carried out in the form of preliminary activities, core activities and closing activities using the inquiry learning learning model. In addition, there is punishment through an inner approach in the form of dhikr, istighfar as well as reciting the Koran and rewards in the form of giving stars that will affect grades, pocket money and motivational writing in notebooks. There are three elements that form the role of social studies educators, namely knowing goodness, loving kindness and doing good. The inhibiting factors come from the students themselves, family, school environment factors, association and technology. While the supporting factors that really help educators in improving the morals of students' manners after online learning come from the character traits possessed by students, families who have formed personalities from an early age as well as motivation and encouragement from educators.